2011
DOI: 10.3390/ijms12021334
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 4 Is Differentially Expressed between Ovarian Cancer Subtypes and Plays a Role in Spheroid Formation

Abstract: Claudin 4 is a cellular adhesion molecule that is frequently overexpressed in ovarian cancer and other epithelial cancers. In this study, we sought to determine whether the expression of claudin 4 is associated with outcome in ovarian cancer patients and may be involved in tumor progression. We examined claudin 4 expression in ovarian cancer tissues and cell lines, as well as by immunohistochemical staining of tissue microarrays (TMAs; n = 500), spheroids present in patients’ ascites, and spheroids formed in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
0
24
1
Order By: Relevance
“…In ovarian cancer patients, carcinoma cells residing within peritoneal fluids adhere to each other and form multicellular suspended cell clusters (41, 42) (Figure 2A). Similarly in our model, we observed that within a 24-hour period, FNE-m-p53 cells, but not control cells, formed compacted cell clusters in suspension (Figure 2A and Supplemental Figure 2A), raising the possibility that m-p53 expression promotes cell-cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…In ovarian cancer patients, carcinoma cells residing within peritoneal fluids adhere to each other and form multicellular suspended cell clusters (41, 42) (Figure 2A). Similarly in our model, we observed that within a 24-hour period, FNE-m-p53 cells, but not control cells, formed compacted cell clusters in suspension (Figure 2A and Supplemental Figure 2A), raising the possibility that m-p53 expression promotes cell-cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional (3D) systems such as multicellular tumor spheroids better reflect the behavior of cells in tumors and, interestingly, claudins have been implicated in spheroid formation. 36 We therefore used a 3D spheroid ovarian cancer model to test whether claudin-6 could also be used as a receptor under these conditions. Interestingly, multicellular tumor spheroid of UCI-101 cells (which express claudin-6, but not claudin-3 or -4) were sensitive to CPE, demonstrating that spheroid formation did not impede the ability of CPE to interact with claudin-6 and induce cell death.…”
Section: Discussionmentioning
confidence: 99%
“…At a specificity of 98%, the claudin-4 and CA125 tests had sensitivities of 51 and 71%, respectively, and the two tests were strongly correlated (Li et al, 2009a). Claudin-4 was further shown to be involved in spheroid formation in ovarian carcinoma (Boylan et al, 2011), as well as in angiogenesis (Li et al, 2009b). Claudin-7 was recently shown to promote invasion of ovarian carcinoma cells in vitro , whereas migration was inhibited (Dahiya et al, 2011).…”
Section: Epithelial Markers Targeted By Emtmentioning
confidence: 99%